WEBSITE DESIGN ACADEMY APPLICATIONS FANTASSY INDOSIAR 2 USING MACROMEDIA DREAMWEAVER MX - Fitri Rahayu; Linda Wahyu Widianti, Skom., MMSI Linda Wahyu Widianti, Skom., MMSI (Jurnal Sistem Informasi, 2007)
Scientific Writing is about designing Websites Indosiar Fantasy Academy 2 in whichthe academia to discuss about the profile, faculty profiles second AFI, AFI history,and news. With Scientific Writing is expected to provide information about the AFI 2are accompanied by pictures so expect a lot of AFI two lovers who see this website asone means to obtain information about the AFI 2.